2023
DOI: 10.1007/s10072-023-06598-y
|View full text |Cite|
|
Sign up to set email alerts
|

Gender-specific outcomes of deep brain stimulation for Parkinson’s disease — results from a single movement disorder center

Abstract: Introduction and goal The investigation of gender differences in treatment response is crucial for effective personalized therapies. With only 30%, women are underrepresented in trials for deep brain stimulation (DBS) in Parkinson’s disease (PD). It is therefore important to evaluate gender-specific outcomes of DBS in PD in order to improve therapeutic counseling. Methods We analyzed clinical outcome parameters of 203 patients with PD that underwent DBS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…STN-DBS improves the non-motor symptoms as measured by the Non-Motor Symptoms Scale (NMSS) total score ( 16 , 45 ), regardless of gender, but women improved significantly on the questions on attention and memory and men on the questions on mood and apathy and perceptual problems and hallucinations ( 16 ). However, when looking at non-motor symptoms as measured by UPDRS part I, two studies found no significant improvement for neither men nor women after STN-DBS ( 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…STN-DBS improves the non-motor symptoms as measured by the Non-Motor Symptoms Scale (NMSS) total score ( 16 , 45 ), regardless of gender, but women improved significantly on the questions on attention and memory and men on the questions on mood and apathy and perceptual problems and hallucinations ( 16 ). However, when looking at non-motor symptoms as measured by UPDRS part I, two studies found no significant improvement for neither men nor women after STN-DBS ( 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that STN-DBS does not lead to a decline in general cognitive abilities ( 38 , 39 ), one study found that male gender was a predictive factor for the development of dementia after STN-DBS ( 40 ). In addition, another study found that only women showed significant improvement on cognitive tests after STN-DBS ( 26 ). While one study reported improvement in the cognitive domain of the quality of life scale PDQ-39 after STN-DBS ( 28 ), another study found no difference in the cognitive domain of the PDQ-39 between genders ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations